2013
DOI: 10.1120/jacmp.v14i2.4011
|View full text |Cite
|
Sign up to set email alerts
|

Dose calculation differences between Monte Carlo and pencil beam depend on the tumor locations and volumes for lung stereotactic body radiation therapy

Abstract: Stereotactic body radiation therapy (SBRT) has been increasingly used as an efficacious treatment modality for early‐stage non‐small cell lung cancer. The accuracy of dose calculations is compromised due to the presence of inhomogeneity. For the purpose of a consistent prescription, radiation doses were calculated without heterogeneity correction in several RTOG trials. For patients participating in these trials, recalculations of the planned doses with more accurate dose methods could provide better correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
4
40
2
Order By: Relevance
“…A future study with a larger sample size of patients is necessary to confirm our observation of the tumor volume independence for centrally located tumors. In contrast to previous studies, (9) the ratios of D1,D99, and D1 of the PTV between the PB and MC calculations were similar for the centrally and peripherally located tumors, suggesting dose differences between the PB and MC calculations do not depend on tumor location for IMRT plans.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A future study with a larger sample size of patients is necessary to confirm our observation of the tumor volume independence for centrally located tumors. In contrast to previous studies, (9) the ratios of D1,D99, and D1 of the PTV between the PB and MC calculations were similar for the centrally and peripherally located tumors, suggesting dose differences between the PB and MC calculations do not depend on tumor location for IMRT plans.…”
Section: Discussioncontrasting
confidence: 99%
“…A simple rescaling can be applied to the volume/dose endpoints when considering radiation treatment related toxicity to the lungs. Previous studies reported that PB calculations overestimated MLD by 7% when compared to MC calculations for centrally located tumors, (16) and by 5% for patients with the peripheral tumors (9) . However, no significant differences were observed between the PB and MC calculations for the MLD in our patient samples.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations